Association between Hemoglobin Levels and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: A Cross-Sectional Study Using Electronic Health Records - Jun Yang; Pi-jun Yan; Qin Wan; Hua Li (Journal of Diabetes Research)
Objective. To investigate the relationship between hemoglobin levels and diabetic peripheral neuropathy (DPN) in type 2 diabetes mellitus (T2DM). Methods. 1511 patients with T2DM were included in the study. DPN was diagnosed based on symptoms, signs, and laboratory tests. Hemoglobin was defined as both a continuous variable and a quartile category variable. We compared patient characteristics between the no diabetic peripheral neuropathy (NDPN) and DPN groups. Logistic regression was conducted to investigate the association of DPN with hemoglobin in all T2DM patients. Linear regression was also performed to investigate the impact of hemoglobin on the vibrating perception threshold (VPT). Results. Compared with the NDPN group, hemoglobin level in the DPN group was significantly lower (118.54 ± 16.91 versus 131.62 ± 18.32 g/L, P<0.01). The prevalence of DPN increased by 50.1% (95% CI: 42.2–57.0%; P<0.001) per standard deviation decrease in hemoglobin. Compared to the highest quartile of hemoglobin, the lower quartiles were associated with a significantly increased risk of DPN in the entire T2DM population (all P<0.01). A per unit decrease in hemoglobin leads to a 0.12 (95% CI: 0.07–0.168) unit increase in VPT after adjustment for possible confounders (P<0.001). Conclusions. Lower hemoglobin levels were associated with increased prevalence of DPN and higher VPT.